Diagnosis of Sinus Histiocytosis with Massive Lymphadenopathy (Rosai-Dorfman Disease) by Fine Needle Aspiration Cytology in a Paediatric patient - Dr. Neema Ankur Rana; Dr. Durva Vijaykumar Patel; Dr. Hiral Samir Shah; Dr. Meena Rajiv Daveshwar (Tropical Journal of Pathology and Microbiology, 2021)
Rosai-Dorfman Disease (RDD) is also known as Sinus Histiocytosis of Massive Lymphadenopathy (SHML). Clinically Rosai-Dorfman Disease is characterized by massive, painless, bilateral cervical lymph node enlargement, often mimics lymphoma. Microscopically, it shows dilatation of lymphatic sinuses occupied by numerous lymphocytes and proliferation of histiocytes with abundant pale eosinophilic cytoplasm containing engulfed lymphocytes or plasma cells- emperipolesis.